Profound Alpha-Fetoprotein Elevation in Hepatocellular Carcinoma with Concomitant Cirrhosis: A Case Report - Fadhilaturrizqie Siregar; Efrida (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Hepatocellular carcinoma (HCC) is a primary liver cancer that often arises in the setting of chronic liver disease, most commonly cirrhosis. Alpha-fetoprotein (AFP) is a tumor marker frequently elevated in HCC, but its diagnostic performance varies. We present a case of HCC with concomitant cirrhosis and a significant elevation of AFP. Case presentation: A 30-year-old male presented with hematemesis, abdominal distension, and jaundice. He had a history of heavy alcohol consumption. Physical examination revealed anemia, icterus, hepatomegaly, and palmar erythema. Laboratory investigations showed elevated AFP (>400 IU/mL), reactive hepatitis B surface antigen (HBsAg), anemia, coagulopathy, and liver dysfunction. Imaging studies confirmed HCC and cirrhosis. This case highlights the diagnostic value of AFP in HCC, particularly when combined with clinical and imaging findings. The patient's history of alcohol abuse and HBsAg positivity are well-established risk factors for both cirrhosis and HCC. The marked elevation of AFP, along with the characteristic imaging features, strongly supported the diagnosis of HCC. Conclusion: AFP remains a valuable tool in the diagnosis and monitoring of HCC, especially in patients with cirrhosis. However, it is essential to interpret AFP levels in conjunction with other clinical and laboratory data to ensure accurate diagnosis and timely management.